Representações Sociais dos Acadêmicos de Administração sobre Recursos Humanos. - Angela Beatriz Busato Scheffer; Daniele dos Santos Fontoura; Carolina Freddo Fleck Fleck; Leticia Weber (REGE Revista de Gestão, 2013)
The theory of social representations has revealed to be useful for allowing an approximation between collective practices and symbolic constitution processes in contemporary society. From this perspective, this paper aims to present the findings on the social representations of undergraduate students in Business Administration of three federal universities of Rio Grande do Sul according to the area, the course and professional Human Resources (HR). The research was structured to cover scholars and teachers of Business Administration courses; here we present only its quantitative part, with business scholars, in which the method used was a survey with application of self-administered questionnaire and analysis of data from the factor analysis technique. A total of 422 questionnaires were applied, of which 419 were considered valid. From the factor analysis we reached eight factors: depreciation of the area, the course and professional human resources; the search for results for the company; isolated and distant sector from the other areas; professional with aversion to numbers; professional having to like people; sector related to the work of psychologists; a protective sector for employees and a sector to investigate the employees’ performance. The results found show that students tend to relate their answers to theory and to experiences lived at the time to position themselves. It was found that the more present representations were the ones that relate the human resources professional to a predilection for dealing with people and the ones that identify the area with the task of evaluating the performance of workers.